Assessing the Financial Literacy of Madrasah Principals in Formulating Revenue and Expenditure Budget Plans - Abdul Haris; Mulyadi Mulyadi; Sutiah Sutiah (STAI Hubbulwathan Duri, 2024)
This research aims to analyze and understand the level of financial literacy of Madrasah Principals in preparing the Madrasah Revenue and Expenditure Budget Plan (RAPBM) in Raudlatul Athfal (RA) Pasuruan Regency, East Java. The formulation of the problem in this research is whether there is an influence on the financial literacy of Madrasah Principals in preparing the Madrasah Revenue and Expenditure Budget Plan (RAPBM). This research uses a quantitative approach. The data source comes from Madrasah Principals. With data collection techniques through questionnaires and documentation. Then tested with simple linear regression analysis. The results found the regression coefficient value of 0.18 (positive), the correlation value was 0.029, the R square value was 0.116 (11.6%), and the significance value was 0.029 0.05, meaning that there was an effect of the financial literacy level of the Madrasah Principals in develop a Madrasah Revenue and Expenditure Budget Plan (RAPBM) in Raudlatul Athfal (RA) of East Java Pasuruan Regency. Thus, the better financial literacy, the better the preparation of the RAPBM.